2022
DOI: 10.1002/cfp2.1138
|View full text |Cite
|
Sign up to set email alerts
|

The alpha and omega of financial risk‐tolerance assessment

Abstract: Over the past three decades, numerous scaling and attitudinal measurement techniques have been developed to facilitate the assessment of an individual's financial risk tolerance. Cronbach's alpha has traditionally been used as the primary measure of scale reliability for assessment tools that have been developed using classical psychometric theory. Recently, however, psychometricians have raised concerns about the ongoing use of Cronbach's alpha as a robust measure of scale reliability. In its place, some have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 42 publications
0
9
0
1
Order By: Relevance
“…Selain itu, uji reliabilitas dengan pendekatan McDonald Omega menghasilkan nilai 0.853 (>0.7) sehingga dapat dikatakan reliabel. Penggunaan reliabilitas McDonald Omega digunakan untuk mengoreksi kelemahan pada rumus Alpha-Cronbach (Heo et al, 2022).…”
Section: Hasil Dan Pembahasanunclassified
“…Selain itu, uji reliabilitas dengan pendekatan McDonald Omega menghasilkan nilai 0.853 (>0.7) sehingga dapat dikatakan reliabel. Penggunaan reliabilitas McDonald Omega digunakan untuk mengoreksi kelemahan pada rumus Alpha-Cronbach (Heo et al, 2022).…”
Section: Hasil Dan Pembahasanunclassified
“…Investors who are risk tolerant can accept more risk and uncertainty when making financial decisions (Finke & Huston, 2003). A large amount of literature has shown that financial risk preference plays an important role in individuals' stock market participation and portfolio decisions (Heo et al, 2022; Hong et al, 2004; Lim & Kim, 2018; Pinjisakikool, 2018; Vissing‐Jørgensen & Attanasio, 2003). Financial risk preference is a situational trait within this study that is directly connected to investors' financial decisions.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…In alignment with what has been reported in the literature, the average score fell between 27 and 28. Over a wide variety of studies, the scale has shown acceptable levels of validity and reliability (see Nunnally and Bernstein (1994) for standards of acceptability), with Cronbach's alpha scores ranging from 0.70 to over 0.80 (Heo et al 2022;Kuzniak et al 2015). In this study, Cronbach's alpha scores varied based on the age of a respondent.…”
Section: Variablesmentioning
confidence: 99%
“…Those with a greater degree of risk tolerance are more likely to obtain higher returns in exchange for more risk (Brayman et al 2017;Nguyen et al 2019;Reddy and Mahapatra 2017). The extant literature suggests that financial knowledge and financial risk tolerance are positively associated (Heo et al 2022;Hermansson and Jonsson 2021).…”
Section: Introductionmentioning
confidence: 99%